Menilik Penerapan Teori Hukum Progresif dalam Sengketa Hak Asuh Anak: Analisis Kasus Putusan No. 0334/Pdt.G/2019/PA.Gdt - Falah, Mohammad Bachrul; Siswanto; Ikhwan, Muhammad; Yurievna, Gritcenko Lyubov (Alauddin Law Development Journal (ALDEV), 2024)
Article 105 of the Compilation of Islamic Law grants child custody primarily to the mother, ensuring the child's welfare. However, Decision No. 0334/Pdt.G/2019/PA.Gdt diverges from this, granting partial custody to the father. This research employs Sadjipto Rahardjo's progressive legal theory to analyze the decision. Despite the contradiction with Article 105, the decision embodies progressive legal values. The judge courageously adopts a joint custody model, prioritizing the child's welfare and justice. This approach allows both parents to care for the child, preserving the child's bond with each parent. The research contributes by showcasing how progressive legal principles can shape custody decisions, ultimately enhancing justice.